A method for preparing a high-sensitivity and high-selectivity gas sensor based on NiMn2O4
Patent Information
- Application Number
- CN202510466621.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2026-10-23
AI Technical Summary
在实验中,一步高温煅烧法制备的NiMn2O4易产生杂相,无法得到纯NiMn2O4,导致材料纯度低、氧空位分布不均
本发明通过材料设计与工艺创新,实现了基于尖晶石结构NiMn2O4纳米颗粒的室温三甲胺气体传感器的多项突破性技术效果。利用硝酸镍和氯化锰为原料,通过独特的两步热解工艺(氮气预烧350 ℃+空气煅烧700 ℃)成功合成NiMn2O4两步热解法通过低温预烧抑制杂相生成,高温煅烧精准调控氧空位浓度,使其具有室温气敏检测特性,工艺重复性高,适合规模化合成。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of gas sensor technology, specifically to a high-sensitivity room-temperature trimethylamine (TMA) gas sensor based on spinel-structured nickel manganese oxide (NiMn2O4) nanoparticles and its preparation method. This sensor is suitable for food freshness monitoring, medical diagnosis, and environmental safety detection. Background Technology
[0002] Trimethylamine (TMA) is a colorless volatile organic compound (VOC) with a strong fishy odor, widely present in food spoilage, industrial emissions, and human metabolism. As a key biomarker for fish and seafood spoilage, TMA concentration directly reflects food freshness, making its detection crucial for food quality monitoring. Furthermore, TMA is a respiratory biomarker for chronic kidney disease (CKD); a TMA concentration exceeding 0.2 ppm in the patient's exhaled breath is sufficient for diagnosis. However, TMA itself is highly toxic; long-term exposure can cause headaches, nausea, respiratory damage, and even liver and kidney dysfunction. Its vapor, when mixed with air, easily forms an explosive gas, posing serious safety hazards in high-temperature or open-flame environments. Therefore, developing a highly sensitive, highly selective TMA gas sensor that can operate at room temperature is of great significance for food safety, medical diagnosis, and environmental safety monitoring.
[0003] Currently, the main methods for detecting trimethylamine include chromatography, mass spectrometry, electrochemical methods, and semiconductor sensor methods. Chromatography and mass spectrometry, including gas chromatography (GC), high-performance liquid chromatography (HPLC), and ion mobility spectrometry (IMS), can achieve accurate quantitative analysis of trimethylamine, but they are heavily reliant on large instruments, complex to operate, expensive, and difficult to monitor in real time, limiting their application in on-site detection. Electrochemical sensors, based on enzymes or noble metal catalysts, while possessing high sensitivity, suffer from limitations: enzyme activity is easily affected by environmental factors (temperature, pH), noble metals are expensive, and the sensors have short lifespans, making it difficult to meet the practical requirements for long-term stable detection.
[0004] Metal-oxide-semiconductor (MOS) sensors, represented by n-type semiconductor materials such as ZnO, SnO2, and WO3, detect gases by inducing resistance changes through surface oxygen adsorption-desorption reactions. While these sensors are low-cost and easy to integrate, they suffer from two major bottlenecks: First, traditional MOS sensors require activation of surface oxygen species at 100–300 °C to enhance gas-sensing reactivity. This high temperature limit their application in portable devices, and the high-temperature environment may also pose a risk of trimethylamine explosion. Second, traditional MOS sensors exhibit poor selectivity and sensitivity. Trimethylamine molecules share similar physicochemical properties with other volatile organic compounds (such as ethanol, acetone, and ammonia), making the sensors susceptible to interference and leading to false alarms.
[0005] Spinel oxides, due to their unique crystal structure and tunable oxygen vacancy characteristics, are considered potential materials for overcoming the aforementioned bottlenecks. Their three-dimensional ion channels can accelerate gas diffusion, while the synergistic effect of tetrahedral and octahedral metal ions can optimize surface reactivity. However, the inherent high-temperature operating conditions of metal oxide semiconductor gas sensors remain unresolved. NiMn2O4, as a bimetallic spinel material, combines the catalytic activity of Ni²⁺ with that of Mn. 3 + / Mn 4+ The multivalent state properties of NiMn2O4 have been applied in supercapacitors and catalysis, but its gas-sensing performance remains unexplored. In experiments, NiMn2O4 prepared by a one-step high-temperature calcination method easily generates impurities, making it impossible to obtain pure NiMn2O4, resulting in low material purity and uneven oxygen vacancy distribution. More importantly, current research lacks in-depth analysis of the band structure of NiMn2O4 and the room-temperature gas-sensing reaction mechanism, which restricts its performance optimization.
[0006] To address the aforementioned issues, this invention proposes an innovative two-step pyrolysis method for preparing high-purity NiMn2O4 nanoparticles. By precisely controlling the oxygen vacancy concentration and mesoporous structure, it achieves, for the first time, highly efficient detection of trimethylamine at room temperature (25 °C). Compared with traditional processes, the nitrogen pre-calcination step (350 °C) effectively suppresses the formation of impurity phases, while the secondary calcination in air (700 °C) constructs a pure-phase spinel structure, simultaneously forming a mesoporous structure and a uniform particle size of 70 nm, significantly improving gas diffusion efficiency. Material characterization shows that the abundant chemisorbed oxygen and oxygen vacancies on the NiMn2O4 surface provide highly active reaction sites for trimethylamine molecules. Test results show that the sensor achieves a response value of 40 for 500 ppm trimethylamine, with a response / recovery time of only 6 seconds / 1 second, and exhibits excellent linearity (R0) in the range of 20–500 ppm. 2 =0.999). Furthermore, its response ratio to 13 interfering gases (such as benzaldehyde and acetone) is below 5.89, demonstrating excellent selectivity. Mechanistic studies show that the low ionization energy (7.82 eV) and weak CN bond strength (307 kJ / mol) of trimethylamine make it more readily oxidized with the NiMn2O4 surface, while the spinel structure's electron transport channels further accelerate charge transfer. This breakthrough not only solves the room-temperature operating problem of traditional metal oxide gas sensors but also provides an efficient and low-power technical solution for food safety monitoring and medical diagnosis.
[0007] In view of this, the present invention proposes an innovative solution. NiMn2O4 with a spinel structure was successfully synthesized via a two-step pyrolysis method involving room temperature magnetic stirring, high-speed centrifugation, and testing its gas-sensing performance. This material represents the first application of NiMn2O4 in the field of gas sensing, filling the technological gap in high-performance room temperature trimethylamine sensors and possessing broad application prospects. Summary of the Invention
[0008] This invention discloses a highly sensitive room-temperature trimethylamine (TMA) gas sensor based on spinel-structured NiMn2O4 nanoparticles and its preparation method. NiMn2O4 nanoparticles were prepared by a two-step pyrolysis process using nickel nitrate and manganese chloride raw materials at room temperature with magnetic stirring. Gas sensitivity testing results show that the sensor exhibits excellent selectivity for TMA among 13 volatile organic compounds at room temperature, with a response intensity of 40, response and recovery times of 6 seconds and 1 second, respectively, and a detection linear range of 20–500 ppm (R0). 2 =0.999).
[0009] To achieve the above objectives, the present invention provides the following technical solution: Preparation methods of gas-sensitive materials and sensors: a. Weigh 1 mole of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and manganese chloride tetrahydrate (MnCl2·4H2O); b. Place the mixed sample from step a into a beaker, add deionized water, and stir magnetically for 2 hours (600 r / min) at room temperature. c. While continuously stirring, add 1 mole of sodium carbonate solution (Na2CO3) dropwise to the mixed solution from step b. d. Stir the turbid solution from step c magnetically for 24 hours at room temperature; e. After the solution from step d has stood for two hours, use a dropper to remove the precipitate and put it into a centrifuge tube. Rinse the tube three times with deionized water and then place it in an electric heating drying oven to dry. f. Take out the sample dried in step e, put it into an agate mortar and grind it for 30 minutes, then put the ground powder into a porcelain boat; g. Place the ceramic boat from step f into a chemical vapor deposition tube furnace for a two-step pyrolysis treatment. In the first pyrolysis treatment, under a nitrogen atmosphere (nitrogen flow rate of 0.3 L / min in the experiment), set the heating temperature, holding time, and other key parameters. Select a rate of 5 °C / min to raise the temperature from room temperature to the target temperature, and hold the material at 350 °C for 3 hours. After 3 hours, allow it to cool naturally to room temperature inside the tube furnace. h. The sample that has undergone the first step of pyrolysis in step g is placed again in a chemical vapor deposition tube furnace for a second pyrolysis treatment, and held at 700 °C in air for 3 hours. After 3 hours, it is allowed to cool naturally to room temperature inside the tube furnace; i. Take out the sample obtained after annealing in step h, grind it thoroughly in an agate mortar for 20 minutes to obtain powder, then mix it with a certain ratio (powder to water ratio 4:1) of deionized water and continue grinding to obtain a uniformly dispersed solution. Use a dropper to evenly drop it onto the interdigitated electrode sheet, and after drying at room temperature for 24 hours, a gas sensor based on metal oxide semiconductor is made. This invention application provides a highly sensitive and selective gas sensor based on NiMn2O4, which is prepared according to the above method.
[0010] Beneficial technical effects of the present invention: This invention achieves several breakthroughs in the technology of a room-temperature trimethylamine gas sensor based on spinel-structured NiMn2O4 nanoparticles through material design and process innovation. Using nickel nitrate and manganese chloride as raw materials, NiMn2O4 is successfully synthesized via a unique two-step pyrolysis process (nitrogen pre-calcination at 350 °C + air calcination at 700 °C). The two-step pyrolysis method suppresses impurity phase formation through low-temperature pre-calcination and precisely controls oxygen vacancy concentration through high-temperature calcination, resulting in a room-temperature gas-sensitive detection characteristic. The process exhibits high repeatability and is suitable for large-scale synthesis.
[0011] The NiMn2O4 nanoparticles synthesized by this invention via a two-step pyrolysis method possess a unique spinel structure and exhibit mesoporous characteristics, providing abundant adsorption sites for gas molecules and thus enabling excellent room-temperature sensing performance. Firstly, the sensor operates efficiently at room temperature (25 °C), achieving a response value of 40 for 500 ppm trimethylamine, with response and recovery times of only 6 seconds and 1 second, respectively. This completely eliminates the dependence of traditional metal-oxide-semiconductor sensors on high temperatures (100–300 °C), significantly reducing energy consumption and avoiding the explosion risk associated with the flammable environment of trimethylamine. In terms of selectivity, the sensor exhibits extremely strong specific recognition capability for trimethylamine. Its response values to 13 interfering gases, including benzaldehyde, acetone, and ethanol, are all below 5.89. The trimethylamine / aniline response ratio is as high as 38:1, a characteristic attributed to the low ionization energy (7.82 eV) and weak CN bond strength (307 kJ / mol) of the trimethylamine molecule, making it more readily bound to the active sites on the NiMn2O4 surface. Furthermore, the sensor exhibits excellent linear response in the range of 20–500 ppm (fitting equation y = 0.079 × ± 0.073, R0). 2With a resolution of 0.999, this sensor covers a full range of detection needs, from food spoilage to industrial leaks. It can be integrated into portable detectors, smart packaging, and medical diagnostic equipment, and applied to seafood cold chain monitoring, chronic kidney disease breath screening, and chemical safety monitoring. This drives the industry towards low-energy consumption and high-precision operation, offering significant economic and social benefits. Attached Figure Description
[0012] Figure 1 Scanning electron microscope (SEM) image of the NiMn2O4 material prepared in this invention; Figure 2 This is the elemental analysis mapping diagram of the NiMn2O4 material prepared in this invention; Figure 3 Transmission electron microscope (TEM) image of the NiMn2O4 material prepared for this invention; Figure 4 The X-ray diffraction (XRD) pattern of the NiMn2O4 material prepared in this invention; Figure 5 The Fourier transform infrared (FTIR) spectrum of the NiMn2O4 material prepared in this invention is shown below. Figure 6 Radar image of the NiMn2O4 material prepared in this invention for 13 gases including acetonitrile, ethanol, hydrazine and trimethylamine at room temperature (25 °C); Figure 7 The response recovery curve of the NiMn2O4 material prepared in this invention to trimethylamine is shown. Figure 8 The response curves of the NiMn2O4 material prepared in this invention to fourteen concentration gradients of trimethylamine from 500 ppm to 20 ppm are shown. Figure 9 The response fitting curves of trimethylamine in the NiMn2O4 material prepared in this invention are shown for fourteen concentration gradients from 500 ppm to 20 ppm. Detailed Implementation
[0013] The following is a detailed description of various exemplary embodiments of this invention. This description illustrates alternative embodiments of this invention; however, it is more clearly stated that this invention can be implemented in various forms and is not intended to limit the invention. Rather, these specific embodiments are provided to increase the completeness and thoroughness of the invention and to clearly and fully convey the scope of this invention to those skilled in the art.
[0014] The terminology used in this application is not intended to limit the scope of the application, but is merely for describing the embodiments. The singular forms “a,” “the,” etc., used in this application and the claims are intended to represent more than one form, but to encompass multiple forms. Open-ended terms such as “having,” “comprising,” etc., used herein mean including but not limited to, unless specifically stated otherwise.
[0015] The numerical ranges used herein do not specifically refer to or represent any particular intermediate value, but rather encompass every intermediate value within that specific range. Any stated value or every smaller range within a stated range is also included in this application.
[0016] Unless otherwise specified herein, all technical and scientific terms used herein have the same meaning as understood by one of ordinary skill in the art. While only preferred materials and embodiments have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0017] The following is a detailed description of a method for preparing a highly sensitive and selective gas sensor based on NiMn2O4, with reference to the accompanying drawings: Example
[0018] The method for preparing a highly sensitive and selective gas sensor based on NiMn2O4 in this invention application includes: a. Weigh out nickel nitrate hexahydrate and manganese chloride tetrahydrate; b. Place the mixed sample from step a into a beaker, add deionized water, and stir magnetically for 2 hours (600 r / min). c. Add sodium carbonate solution dropwise to the mixed solution from step b; d. Stir the solution from step c for 24 hours; e. After the solution from step d has been allowed to stand, the precipitate is aspirated and placed into a centrifuge tube. The tube is then rinsed three times with deionized water and placed in an electric heating drying oven for drying. f. Take out the dried sample from step e and grind it in an agate mortar for 30 minutes. Then put the ground powder into a porcelain boat. g. The ceramic boat from step f is placed in a chemical vapor deposition tube furnace for a two-step pyrolysis treatment. The first pyrolysis is carried out in a nitrogen atmosphere at a heating rate of 5 °C / min to 350 °C, held at that temperature for 3 hours, and then allowed to cool naturally to room temperature in the tube furnace. h. The sample that has completed the first step of pyrolysis in step g is placed again in a chemical vapor deposition tube furnace for a second pyrolysis treatment. It is kept at 700°C in air for 3 hours, and then naturally cooled to room temperature in the tube furnace. i. After taking out the sample obtained in step h, grind it thoroughly with an agate mortar and pestle. Mix the powder obtained with deionized water and continue grinding. Use a dropper to evenly drop it onto the interdigital electrode plate. After drying at room temperature for 24 hours, a gas sensor is obtained.
[0019] Example 2: like Figure 1 The SEM images shown reveal the morphology of the material. The sample shown in Figure a exhibits spherical and platelet-like nanoparticle morphologies, with an average particle size of only 70 nm. The high-magnification image in Figure b further demonstrates the presence of micron-sized pores and a rough structure on the particle surface, significantly increasing the material's specific surface area. Simultaneously, elongated gaps form between the particles, extending into narrow slit-like pores in three-dimensional space, providing numerous rapid gas diffusion paths for trimethylamine and enhancing the material's gas-sensitive response speed.
[0020] Example 3: Figure 2 The mapping diagram shows that the sample has abundant Ni, Mn and O elements, and the elements are evenly distributed, confirming that the material was successfully synthesized.
[0021] Example 4: Figure 3 The image below is a TEM image of NiMn2O4. As can be seen from the image, the material is composed of uniformly dispersed nanoparticles. Figure 3 (cd) shows clear lattice fringes with interplanar spacings of d. (111) =0.456 nm, d (220) =0.295 nm. Figure 3 The inset in d is a selected area electron diffraction (SAED) pattern, which shows that the sample has a polycrystalline structure.
[0022] Example 5: Figure 4 The image below shows the XRD pattern of NiMn2O4. According to the image, we can see that the material has diffraction peaks at 35.412° and 43.037°, which correspond to the (311) and (400) crystal planes of the sample, respectively.
[0023] Example 6: Figure 5 The Fourier transform infrared spectrum was used to study the functional groups of the sample. The sample has abundant functional groups, which provide active sites for gas adsorption, thus exhibiting high sensitivity.
[0024] Example 7: Figure 6To connect the AES-4SD power supply of the optoelectronic integrated test platform, the sensor's response to target gases such as hydrogen peroxide, acetonitrile, methanol, hydrazine, ammonia, ethylenediamine, ethanol, and trimethylamine was tested at room temperature (25°C, 30% relative humidity) with a bias voltage of 4 V. It was found that the gas sensor prepared in this invention exhibits high sensitivity and selectivity to trimethylamine.
[0025] Example 8: pass Figure 7 It can be seen that the sample's response intensity to trimethylamine is 40, and the response and recovery times are 6 seconds and 1 second, respectively.
[0026] Example 9: pass Figure 8 It can be seen that the sensing limit of the sample for trimethylamine reaches 20 ppm, and the response value is 2.
[0027] Example 10: pass Figure 9 It can be seen that the sample fits the trimethylamine concentration gradient very well, with a fitting function y = 0.079 ± 0.073 and R0. 2 =0.999.
[0028] The above describes typical embodiments of the present invention. However, the present invention is not limited to the use of the above embodiments, and various modifications or changes can be made within the scope of the claims. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. Preparation method of gas-sensitive materials: a. Weigh out nickel nitrate hexahydrate and manganese chloride tetrahydrate in equimolar ratio; b. Place the mixed sample obtained in step a into a beaker, add deionized water and stir thoroughly for 2 hours (600 r / min). c. Add 1 molar sodium carbonate solution dropwise to the turbid solution obtained in step b while stirring continuously; d. Stir the turbid solution obtained in step c magnetically for 24 hours at room temperature; e. After letting the solution from step d stand for two hours, rinse the precipitate three times with deionized water, and then place it in an electric heating drying oven for drying. f. Take out the sample dried in step e and grind it for 30 minutes, then put the ground powder into a porcelain boat; g. Place the ceramic boat from step f into a chemical vapor deposition tube furnace for a two-step pyrolysis treatment. The first pyrolysis treatment is carried out at 350 °C for 3 hours in a nitrogen atmosphere. After 3 hours, allow it to cool naturally to room temperature inside the tube furnace. h. The sample that has undergone the first step of pyrolysis in step g is placed again in a chemical vapor deposition tube furnace for a second pyrolysis treatment, and held at 700 °C in air for 3 hours. After 3 hours, it is allowed to cool naturally to room temperature inside the tube furnace; i. Take out the sample obtained after annealing in step h and grind it for 20 minutes to obtain powder. Then mix it with deionized water and continue grinding to obtain a uniformly dispersed solution. Use a dropper to evenly drop it onto the interdigitated electrode sheet. After drying at room temperature for 24 hours, a gas sensor based on metal oxide semiconductor is made.
2. The method for preparing a highly sensitive and selective gas sensor based on NiMn2O4 according to claim 1, characterized in that... In step g, during the two-step nitrogen pyrolysis step, the heating rate of the tubular furnace is 5 °C / min, and the nitrogen flow rate is 0.3 L / min.
3. A highly sensitive and selective gas sensor based on NiMn2O4, characterized in that, Prepared according to the preparation method according to any one of claims 1 to 2.
4. The high-sensitivity and high-selectivity gas sensor based on NiMn2O4 as described in claim 3 has the application of efficient and rapid detection of trimethylamine gas.